2008
DOI: 10.1248/bpb.31.691
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of a Sulfated-Polysaccharide Isolated from the Marine Red Algae Champia feldmannii

Abstract: Sulfated-polysaccharides are complex macromolecular constituents of the extracellular matrix of marine algae that play an important role in mechanical, osmotic and ionic regulation.1) In Biomedicine the anticoagulant and antithrombotic properties have been most widely exploited and, at least for galactans, appear to be dependent on the sulfatation content and/or position of the sulfate groups.2) A natural sulfated polymer of L-fucose (fucoidan) showed a dose-dependent inhibition of leukocyte migration in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 22 publications
3
54
2
Order By: Relevance
“…Hf1s and Hf2s showed more homogeneous bands, with weak metachromasia and, Hf3s showed a poly-disperse polysaccharide with metachromasia intense. These differences in charge density of these algal molecules in were accordance with other studies (Assreuy et al, 2008;Rodrigues et al, 2009b). This suggested that the H. floresia polysaccharides occurred with distinct molecular characteristics in the algal tissue.…”
Section: Agarose Gel Electrophoresissupporting
confidence: 93%
See 2 more Smart Citations
“…Hf1s and Hf2s showed more homogeneous bands, with weak metachromasia and, Hf3s showed a poly-disperse polysaccharide with metachromasia intense. These differences in charge density of these algal molecules in were accordance with other studies (Assreuy et al, 2008;Rodrigues et al, 2009b). This suggested that the H. floresia polysaccharides occurred with distinct molecular characteristics in the algal tissue.…”
Section: Agarose Gel Electrophoresissupporting
confidence: 93%
“…These studies suggested that was interesting to investigate this class of macromolecules in animal models (Mourão and Pereira, 1999;Farias et al, 2001;Zhang et al, 2003;Assreuy et al, 2008;Fonseca et al, 2008;Lins et al, 2009;Ananthi et al, 2010), as valuable tools on development of new pharmacological drugs. The anticoagulant activity of marine algae SPs has been widely reported.…”
Section: Biological Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the galactan isolated from the red marine alga G. crinale presented inflammatory activity in the experimental model of rat paw edema. Inflammatory effects of SP of red algae have already been demonstrated (Di Rosa et al, 1971;Damas, 1980;Pomin & Mourão, 2008;Assreuy et al, 2008Assreuy et al, , 2010Lins et al, 2009). The inflammatory effect of λ carrageenan, already demonstrated in literature, show different profile of response compared to SG-Gc.…”
Section: Discussionmentioning
confidence: 93%
“…The literature has established an association between anti-inflammatory effects of fucans (Aruffo et al, 1991;Weston & Parish, 1991;Blondin et al, 1994;Tissot et al, 2003;Medeiros et al, 2008;Siqueira et al, 2011), the main representative sugar of brown algae (Phaeophyta), and proinflammatory/immunostimulant effects of galactans, the main representative sugar of red algae (Rodophyta). In this line, the sulfated polysaccharide obtained from the red seaweed Champia feldmannii DiazPifferer (Lomentariaceae) stimulated leukocyte migration and paw edema paralleled with increase in vascular permeability in rats (Assreuy et al, 2008) and antitumor effect in mice (Lins et al, 2009). The sulfated polysaccharide of the red seaweed Solieria filiformis Farias (Solieriaceae) also induced paw edema in rats (Assreuy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%